The first step for solving this equation is to collect the like terms with an r variable. -r - 2 = -9 Now move the constant to the right side of the equation and then change its sign. -r = -9 + 2 Calculate the sum on the right side of the equals sign. -r = -7 Then lastly,, change the signs on both sides of the equation to find your final answer. r = 7 This means that the correct answer to your question is going to be r = 7. We can check this by putting 7 where r is in the equation. This means that in order to check this,, our equation will change to the following: -8(7) - 2 + 7(7) = -9 We will first start checking this by multiplying the first two numbers together. -56 - 2 + 7(7) = -9 Now multiply the 7 by the number in the parenthesis. -56 - 2 + 49 = -9 Now use addition and subtraction rules to calculate the expression on the left side of the equals sign. -9 = -9 This tells us that the equality us true because both sides of the equation are identical. Let me know if you have any further questions. :)